Die begrip "rentmeesterskap" in die gemeentebouproses - Merwe, J. F. van der (HTS teologiese studies, 2002)
The concept of stewardship in the process of extending the local churchThis study looks at the biblical principal of stewardship in the context of building up the local church. The study starts with the methodological principles of Practical Theology and various models of the process of building up the local church. Traditionally stewardship was regarded as the principle that encouraged Christians to give monetary contributions towards extending the local church. The study makes it clear that a much broader and biblical understanding of stewardship is necessary. It looks at the different dimensions of stewardship and the effect the stewardship principle has on the Christian’s use of resources, time, spiritual gifts, possessions, as well as on creation, life and the Gospel of Jesus Christ.